Prevalence and characteristics of selective IgA deficiency in celiac patients - Méndez Loayza, Daniela de los Ángeles (2021)
Introduction: Celiac disease is a multisystemic autoimmune disease that mainly affects the small intestine. Selective Immunoglobulin A deficiency is the most common primary immunodeficiency in the general population, with an incidence of 1%. It is estimated that it affects 2%–3% of celiac disease and 6.5% of patients with this deficit have celiac disease, observing the important association between both. Objectives: To determine the prevalence of selective Immunoglobulin A deficiency in celiac patients. Describe the clinical, serological, and histological presentation and its association with autoimmune diseases. Materials and methods: Cross-sectional, descriptive, and retrospective study in celiac patients with Immunoglobulin A dosing in the period from March 2005 to March 2020, at the Gastroenterology Clinic, Hospital de Clínicas, Montevideo-Uruguay. Results: 343 patients were included. Seven patients presented selective Immunoglobulin A deficiency (2%). All were female with a mean age of 20 years (4-36). Selective total immunoglobulin A deficiency was observed in 6 patients (85%) and only 1 (15%) had partial deficiency. Tissue transglutaminase antibody immunoglobulin A and antiendomysium antibody were negative in patients with selective total immunoglobulin A deficiency and positive in those with partial deficiency. All presented villous atrophy, gastrointestinal symptoms, and a lower incidence of autoimmune diseases compared to the reference literature. Conclusions: The prevalence of selective immunoglobulin A deficiency in this celiac population (2%) is similar to that reported in other populations, reaffirming the importance of including immunoglobulin A dosing for the diagnosis of CD.